Empowering Thai Nuns Towards Sustainable Development - Metteyya Beliatte; Yaoping Liu; Chompoo Gotiram; Chatchai Rakthin (Journal of International Buddhist Studies)
Thai nuns, known as Mae Chee who shave their heads, don white clothing, and adhere to a monastic-like lifestyle, have an ambiguous status among Thai Buddhist practitioners. Despite their monastic-like lifestyle, they fall under the official category of laywomen (Upasika). Nevertheless, they are sometimes treated as monastics and some government agencies see them as renunciants, hindering them from receiving full benefits from either category. They encounter societal disadvantages and adverse stereotypes. Their living conditions are inadequate, with restricted options for studying and executing tasks. Scholars think that pursuing official monastic status or reinstating bhikkhuni ordination are the most effective methods to enhance the social standing of these underprivileged women. Religious feminist researchers are leading the cause with the singular aim of attaining equal status to male monastics, without regard for the actual consequence after that goal is realized. Nevertheless, their efforts have not been successful in improving their quality of life, even though they have been struggling for a long time. This research employs critical discourse analysis and thematic analysis of qualitative data obtained through interviews and observations to analyze these efforts through the lens of sustainable development, arguing that these ongoing efforts may not only hinder sustainable development but also push them towards greater subordination within the institutional patriarchy.